Leczenie chirurgiczne wysiłkowego nietrzymania moczu za pomocą zestawu Gynecare TVT Secur™ System – doniesienie wstępne - Baranowski, Włodzimierz; Rogowski, Artur; Doniec, Jacek; Wodzisławska, Agnieszka (Menopause Review/Przegląd Menopauzalny, 2010)
Introduction: Sling procedures were first introduced over 100 years ago in the treatment of stress urinary incontinence. Since then they have evolved to become less invasive and safer. The sling procedure using the Gynecare TVT Secur™ system is a new therapeutic option for women with stress urinary incontinence. Objectives: To evaluate the efficacy and safety of Gynecare TVT Secur™ in the surgical treatment of stress urinary incontinence in women. Material and methods: The study comprised consecutive female patients admitted to the Department of Gynaecology and Gynaecological Oncology of the Military Institute of Health Services in Warsaw, Poland, who had been qualified for surgical treatment of stress urinary incontinence on the basis of physical signs and symptoms and the findings of a urodynamic study. The procedure was performed using the Gynecare TVT Secur™ system with tapes introduced in an H- or U-shape mode. Results: Between October 2006 and September 2009, 77 sling procedures using the Gynecare TVT Secur™ system were performed in women with stress urinary incontinence. Their mean age was 55.1 (30-76) years, mean BMI 28.5 (20.2-43.8) kg/m 2 . Sixty-nine implants were positioned in H-shape mode, 8 in U-shape mode. Forty- nine women (63.6%) were menopausal, 14 (18.2%) previously had three or more natural deliveries, 13 (16.8%) had a history of gynaecological surgeries. Thirty-one procedures were performed under general anaesthesia and 46 under local anaesthesia. The mean duration of the surgery was 9 (4-42) minutes. It was possible to discharge fifty-seven (74%) women on the day of the surgery. Urine retention was observed only in 1 (1.7%) woman. No other complications were recorded. Conclusions: The surgical treatment of urinary incontinence with sling procedures using the Gynecare TVT Secur™ system shows good immediate efficacy and safety. Considering this as well as the short duration of the procedure and its good tolerability under local anaesthesia, use of the Gynecare TVT Secur™ system in an outpatient setting can be advocated. Further studies with longer follow-up are necessary to establish the long-term efficacy of the procedure.